Pengenalan Internet of Things (IoT) sebagai Upaya Peningkatan Kualitas Pegawai Kementerian Pendidikan dan Kebudayaan: Introduction of the Internet of Things (IoT) to Improve the Quality of Civil Servant of the Ministry of Education and Culture - Utomo Budiyanto; Titin Fatimah; Pipin Farida Ariyani (DRPM Universitas Budi Luhur, 2021)
Internet of Things is a term that describes the relationship of an object (things) with other objects through a wireless network such as the internet without requiring interaction with humans. Internet of Things is one of the trends in the world of technology that can be applied in every area of ​​life. This community service activity aims to provide knowledge and understanding of the Internet of Things (IoT) to participants who are Civil Servants within the Ministry of Education and Culture. The method of implementing the activities is carried out through several stages, namely the preparation stage, the implementation stage, and the evaluation stage. As a result of this activity, participants understand the concept and workings of IoT, the functions and benefits of IoT, as well as the advantages and disadvantages of IoT through the examples of the application of IoT in the field of government given. Keywords : internet, IoT, civil servant